Reinterpretation the Meaning of Ahl al-Sunnah wa al-Jamā’ah in the Book of Syarh al-Sunnah by al-Barbahāri: Penafsiran Ulang Makna Ahl al-Sunnah wa al-Jamā’ah pada Kitab Syarh al-Sunnah Karya al-Barbahari - Maulana, Muhammad Al-Fayyadh; abror, indal (Jurnal Living Hadis, 2023)
The debate about the meaning of the term ahl al-sunnah wa al-jamā'ah in the iftirāq al-ummah hadith has not stopped until now. Each group has different views and claims to each other as the most deserving of that status. Al-Barbahari (d. 329 H), one of the figures of the Hanbali school of thought, tried to revive this understanding, but then tried to revive it haphazardly by modern Salafi-Wahhabi groups in order to legitimize the takfiri movement and anti-heresy sentiments. This article explains the views of al-Barbahari in the book Syarḥ al-Sunnah with several basic questions; first, what is al-Barbahari's view in interpreting ahl al-sunnah wa al-jamā'ah?, and second, what is the approach of manhaj wasaṭiyyah al-Azhar in explaining the same term? To analyze this problem, the writer uses descriptive-analytical method through the approach of manhaj al-Azhar al-Syarif and found the fact that Al-Barbahari has the characteristics of thinking that tend to be textual and pragmatic. Thus, there are many discrepancies in the discourse of aqidah, the use of reason in understanding the texts, and the methods of criticism and syarah of hadith are not appropriate.